The effect of melatonin on coagulation parameters in rats with cerulein-induced acute pancreatitis - Ercan Keskin; Deniz Uluışık (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to evaluate possible effects of melatonin on coagulation parameters in rats with cerulein induced acute pancreatitis. Materials and Methods: For this purpose, 32 adult, male, healthy Wistar Abino rats were used. The animals were divided into four groups. Group I animals was no applied. Group II animals was intraperitoneally administered 50 mg/kg melatonin per rat twice for two hours intervals. Animals of group III received two intraperitoneal injections of cerulein (50 μg/kg and 25 μg/kg bw, respectively) at two hours intervals. Animals of group IV received two intraperitoneal injections of cerulein (50 μg/kg and 25 μg/kg bw, respectively) at two hours intervals and the rats received an intraperitoneal injection of 50 mg/kg melatonin 30 min before each cerulein injection. In blood samples taken from all animals, platelet, fibrinogen, activated partial thromboplastin time (APTT), prothrombin time (PT), international normalized ratio (INR) levels were determined. Results: Acute pancreatitis caused increment in platelet count and fibrinogen level compared to control group (p<0.05). APTT, PT and INR were significantly shortened with acute pancreatitis in comparison with control group (p<0.05). Melatonin application to rats with acute pancreatitis importantly lengthened PT and INR compared to acute pancreatitis group (p<0.05). Conclusion: We concluded that melatonin may be alleviated the abnormalities in coagulation parameters resulting from acute pancreatitis.